2018
DOI: 10.1371/journal.ppat.1006940
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic roles of Clostridium difficile sin locus

Abstract: Clostridium difficile is the primary cause of nosocomial diarrhea and pseudomembranous colitis. It produces dormant spores, which serve as an infectious vehicle responsible for transmission of the disease and persistence of the organism in the environment. In Bacillus subtilis, the sin locus coding SinR (113 aa) and SinI (57 aa) is responsible for sporulation inhibition. In B. subtilis, SinR mainly acts as a repressor of its target genes to control sporulation, biofilm formation, and autolysis. SinI is an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 73 publications
(131 reference statements)
4
85
0
Order By: Relevance
“…Cecal supernatants from mice at 20h of infection extracted and subjected to SDS-PAGE and transfer to PVDF membrane (PerkinElmer, Waltham, MA) as described (59)…”
Section: Western Blot For Toxin B Integritymentioning
confidence: 99%
“…Cecal supernatants from mice at 20h of infection extracted and subjected to SDS-PAGE and transfer to PVDF membrane (PerkinElmer, Waltham, MA) as described (59)…”
Section: Western Blot For Toxin B Integritymentioning
confidence: 99%
“…It was suggested that opp and app 542 may be involved in sporulation as a response to nutrient availability. Like csiA, 543 these mutants also show an increase on the expression of the sinRR' operon 544 (Table 3), previously shown to be involved in sporulation, toxin production and 545 motility (Girinathan et al, 2018). It was shown that overexpression of sinR 546 increased sporulation efficiency, while overexpression of sinR' reduced sporulation.…”
mentioning
confidence: 86%
“…Recently, we reported the identification and characterization of master regulator SinR in C. difficile that was found to regulate sporulation, toxin production, and motility (15). SinR in the Gram-positive model organism B. subtilis is well characterized and is known to regulate multiple pathways, including sporulation, competence, motility, and biofilm formation (1618).…”
Section: Introductionmentioning
confidence: 99%
“…In C. difficile also the sin locus is a two-gene operon and encodes for SinR and SinR’. In our initial characterization of the C. difficile sin locus, we have shown that disruption of sin locus (absence of both SinR and SinR’) resulted in asporogenic, less toxic, and less motile phenotype (15). Another study which reports that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation